Implementing Disinflations in a Medium-Scale Dynamic General Equilibrium Model: Money Supply vis-à-vis Interest Rate Rules - Guido Ascari; Tiziano Ropele (Università degli Studi di Pavia, Dipartimento di Economia Politica e Metodi Quantitativi (EPMQ), 2010)
Successful disinflation episodes have been shown to involve a sustained period of output contraction. We revisit the largely debated issue on the costs of different speed and timing of disinflations when monetary policy is implemented either via a money supply rule (MSR) or an interest rate rule (IRR). In terms of transitional costs, cold-turkey IRR disinflations are less expensive than those under MSR, with theoretical sacrifice ratios averaging 1.0 and 2.8 respectively, and are accomplished more rapidly. Gradual and anticipated disinflations deliver further lower sacrifice ratios. From a welfare perspective, despite the temporary economic contraction, disinflations are welfare improving. More interestingly, the overall welfare gain from disinflation is not affected by the actual policy implementation: what really matters is the achievement of a permanent lower inflation rather than how this is practically accomplished.
Keywords: E31; E5; 330; Disinflation; Sacrifice ratio; Nonlinearities